Desenvolvimento de programa livre para análise de pórticos tridimensionais considerando-se a não linearidade geométrica, fissuração do concreto e ligações semi-rígidas - Cotta, Igor Frederico Stoianov (Universidade Federal de São Carlos, 2007)
Structural analysis of framed structures using discrete method, wherein, splitting them into elements with simplified considerations, can bring not satisfactory results or end up using very high safety coefficient to the structure. With the growth of computing and microcomputers it is feasible the resolution of structures considering all parts, therefore three-dimensional. The scope of this work is to make a physical and geometrical non-linear analysis of three-dimensional framed structures with re-bar elements, which can be joined by monolithic or semi-rigid connection, that is commonly used in Precast concrete structures. In order to reach this aim, has been developed a free software using PASCAL language and structural matrix analysis, adding up concrete physical nonlinear analysis with Branson expression. The geometric non-linear was considered from a present Lagrangean formulation. In both cases, it was used the incremental loading technique, which showed a very interesting relation between the results. In order to consolidate the studied concepts and to validate the developed software, it was dedicated a special attention to the resolution of several samples, comparing them with the given results of other software and also with values from experimental analysis, specially for the semi-rigid connections
Keywords: Análise de estruturas; Concreto armado; Fissuração; Software livre; Free software; Three-dimensional frames; Physical non-linearity; Geometric non-linearity; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::TRANSPORTE E TRAFEGO URBANO E REGIONAL